A subpopulation of oxytocin neurons initiate expression of CRF receptor 1 (CRFR1) in females post parturition. (November 2022) - Ugartemendia, Lierni; De Guzman, Rose M; Cai, Jing; Rajamanickam, Shivakumar; Jiang, Zhiying; Tao, Jonathan; Zuloaga, Damian G; Justice, Nicholas J
Abstract: Oxytocin (OT) is essential for successful reproduction, particularly during parturition and lactation. During the postpartum period, OT also influences maternal behavior to promote bonding between mothers and their newborns, and increases stress resilience. However, the mechanism by which stress influences OT neuron activity and OT release has remained unclear. Here, we provide evidence that a subpopulation of OT neurons initiate expression of the receptor for the stress neuropeptide Corticotropin Releasing Factor (CRF), CRFR1, in reproductive females. OT neuron expression of CRFR1 begins at the first parturition and increases during the postpartum period until weaning. The percentage of OT neurons that express CRFR1 increases with successive breeding cycles until it reaches a plateau of 20–25% of OT neurons. OT neuron expression of CRFR1 in reproductive females is maintained after they are no longer actively breeding. CRFR1 expression leads to activation of OT neurons when animals are stressed. We propose a model in which direct CRF signaling to OT neurons selectively in reproductive females potentiates OT release to promote stress resilience in mothers. Highlights: A subpopulation of OT neurons express CRFR1 only in female mice during the perinatal period. CRF increases the activity of CRFR1+ OT neurons. CRFR1 expression by OT neurons starts after parturition, reaches a peak at PP21 and it is maintained after pups are weaned. Psychogenic stress activates OT neurons that co-express CRFR1 only in postpartum females.